Adsorption of Argon on Six Microporous Solids - Roman Wojsz (Adsorption Science & Technology)
An analysis of the function characterizing the structural heterogeneity of microporous adsorbents was presented. The micropore distribution functions f(x), where x is the micropore half-width, were calculated assuming a slit-like model for the micropores and applied to the adsorption of argon on four active carbons, one carbon fibre and one zeolite at 77.3 K.